SISTEM MANAJEMEN STOCK BARANG ANTAR CABANG TOKO CAHAYA LANCAR BERBASIS WEB - Riswanto Halim; Arif Rahman Hakim; Mahfud Al Hayat; Wasis Haryono (Journal of Research and Publication Innovation, 2025)
Cahaya Lancar Store is a trading business engaged in the sale of household furniture, with several branches spread across the South Tangerang area. As the business grows, coordination in managing stock between branches becomes a challenge. So far, stock recording is still done manually in each branch without a system that is interconnected, which often causes differences in data, delays in the distribution of goods, and difficulties in searching for stock between locations. This condition has an impact on employee work efficiency and customer service. To answer these problems, a web-based information system was designed that can be used together by all branches. This system allows automatic and real-time stock recording, and provides features such as submitting requests for goods between branches, notifications when stock is running low, and periodic stock reports. The implementation of this system aims to speed up the flow of goods distribution, minimize recording errors, and simplify the stock monitoring process in all branches. With an integrated system, Cahaya Lancar Store is expected to be able to run operations in a more organized and responsive manner to market needs.